Kajian Pengembangan Web HyLearn oleh Dosen Fakultas Ilmu Pendidikan Universitas Negeri Jakarta - Adjmal QD; Cecep Kustandi; Kunto Imbar (Jurnal Pembelajaran Inovatif, 2020)
Adjmal. The studies of Hylearn web-based development by the lecturers of Faculty of Education Science Universitas Negeri Jakarta This research aims to observe the development studies that has been implemented by the lecturers of faculty of education science Universitas Negeri Jakarta. This research uses the instrument in the form of questionare as a tools to gather the data which used TPACK approach. This research uses TPACK’s framework with the IDL version that consist of 4 aspects (1) Technological aspect (2) Pedagogy technological aspect (3) Content technological aspect (4) Content of pedagogy technological aspect The results are explained based on the used framwork as following (1) Tecnological aspect, a half of (50%) lecturers are able to use Hylear web based for teaching needs (2) Pedagogy technological aspect, more than a half of (54%) lecturers are able to improve the knowledge of teaching’s methods as well as the students (3) Content Technological aspect, more than a half of (60%) lecturers are able to implement instructional’s principle design for the content that’s made, choosen, or used (4) Content of pedagogy technological aspect, more than (60%) lecturers are able to create online learning course that’s effective and efficient with combining the content, technology, and appropriate instructional method.